2011
DOI: 10.1121/1.3651816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cross-language voice training on speech perception: Whose familiar voices are more intelligible?

Abstract: Previous research has shown that familiarity with a talker's voice can improve linguistic processing (herein, "Familiar Talker Advantage"), but this benefit is constrained by the context in which the talker's voice is familiar. The current study examined how familiarity affects intelligibility by manipulating the type of talker information available to listeners. One group of listeners learned to identify bilingual talkers' voices from English words, where they learned language-specific talker information. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 45 publications
4
72
0
Order By: Relevance
“…That some children are better at learning the voices of previously unfamiliar talkers is also relevant for spoken language processing in general. Numerous studies have found that familiarity with a talker’s voice improves spoken language processing in both children (Levi, 2014) and adults (Levi et al, 2011; Magnuson et al, 1995; Nygaard and Pisoni, 1998; Nygaard et al, 1994). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That some children are better at learning the voices of previously unfamiliar talkers is also relevant for spoken language processing in general. Numerous studies have found that familiarity with a talker’s voice improves spoken language processing in both children (Levi, 2014) and adults (Levi et al, 2011; Magnuson et al, 1995; Nygaard and Pisoni, 1998; Nygaard et al, 1994). …”
Section: Discussionmentioning
confidence: 99%
“…All sound files were normalized to have a uniform RMS amplitude. The 3 bilingual talkers used in the current study had similar intelligibility (table 1) and were selected from a larger group of bilinguals (Levi et al, 2011). Additionally, these 3 talkers were selected to have relatively different average fundamental frequency (F0) across productions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All sound files were normalized to have a uniform RMS amplitude. The three bilingual speakers used in the current study were highly intelligible and selected from a larger group of bilinguals (Levi, Winters, & Pisoni, 2011; see Table 1). In addition, the three speakers were selected as having relatively different average fundamental frequency across productions.…”
Section: Methodsmentioning
confidence: 99%
“…Intelligibility refers to the average number of words correctly identified across three signal-to-noise ratios and a clear listening condition (Levi et al, 2011). F0 is the average fundamental frequency at the vowel midpoint for the 360 English words.…”
Section: Figurementioning
confidence: 99%